Methicillin-resistant Staphylococcus aureus (MRSA) screening of hospital dental clinic surfaces - Faden, Asmaa (Saudi J Biol Sci, 2019)
We assessed the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) strains on surfaces of hospital dental clinics. Specimens were obtained from 5 clinically symptoms-free patients of five different specialties clinics (Implantology, Pediatric Dentistry, Prosthetics, Restorative Dentistry, and Oral Medicine) of the Dental Clinic Hospital of King Saud University before and after each patient. A Q-tip swabs were used from 10 surfaces in each clinic (Arm rest of dental chair, floor beneath dental chair, sink/faucet, towel dispenser, instrument table handle, light handle, X-ray viewer, paper dental records, head rest, and bench). Specimens were cultured in CHROMagar MRSA medium. Prevalence of MRSA colonization was compared between periods before and after patients visited each clinic for treatment. The results showed that the prevalence of MRSA was remarkably increased after patients visited the area. The results indicate that dental clinics should be considered as possible reservoirs of MRSA in the hospital setting.